2014
DOI: 10.1105/tpc.114.131698
|View full text |Cite
|
Sign up to set email alerts
|

A Rice KNOX Transcription Factor Represses Brassinosteroid Production in the Shoot Apical Meristem

Abstract: Knotted1-like homeobox (KNOX) transcription factors establish and maintain a population of self-renewing stem cells in the shoot apical meristem (SAM) of flowering plants and thereby direct aerial organ formation and determine inflorescence architecture. KNOX genes are thought to target thousands of loci; however, the relationship between KNOX and most of these loci is unknown (Bolduc et al., 2012). A growing body of evidence suggests that a major function of KNOX transcription factors is to regulate phytohorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Four members of Class I KNOX in Arabidopsis , including SHOOT MERISTEMLESS ( STM ), BREVIPEDICELLUS ( BP , also named KNAT1 ), KN1 -Like in Arabidopsis thaliana 2 ( KNAT2 ), and KNAT6 , play critical roles in establishing and maintaining SAM activity and organ separation during vegetative growth [ 9 ]. Numerous studies have confirmed, also in other species, their functions in SAM formation [ 16 , 17 , 18 ] and lateral organ separation [ 8 , 9 ]. In addition, three KNOX I genes are also involved in wood formation and the adaxial xylem cell differentiation [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 84%
“…Four members of Class I KNOX in Arabidopsis , including SHOOT MERISTEMLESS ( STM ), BREVIPEDICELLUS ( BP , also named KNAT1 ), KN1 -Like in Arabidopsis thaliana 2 ( KNAT2 ), and KNAT6 , play critical roles in establishing and maintaining SAM activity and organ separation during vegetative growth [ 9 ]. Numerous studies have confirmed, also in other species, their functions in SAM formation [ 16 , 17 , 18 ] and lateral organ separation [ 8 , 9 ]. In addition, three KNOX I genes are also involved in wood formation and the adaxial xylem cell differentiation [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 84%